Transgovernance Advancing Sustainability Governance - Meuleman, Louis (Springer Berlin Heidelberg : Imprint: Springer, 2013)
‘Transgovernance: Advancing Sustainability Governance’ analyses  what implications recent and ongoing changes in the relations between politics, science and media – together characterized as the emergence of a knowledge democracy – may have for governance for sustainable development, on global and other levels of societal decision making, and vice versa: How can the discussion on sustainable development contribute to a knowledge democracy? How can concepts such as second modernity, reflexivity, configuration theory, (meta)governance theory and cultural theory contribute to a ‘transgovernance’ approach which goes beyond mainstream sustainability governance? This volume presents contributions from various angles: international relations, governance and metagovernance theory, (environmental) economics and innovation science. It offers challenging insights regarding institutions and transformation processes, and into the paradigms behind contemporary sustainability governance.This book gives the sustainability governance debate a new context. It transforms classical questions into new options for societal decision making and identifies starting points and strategies aimed at effective governance of transitions to sustainability.